Comprehensive identification and profiling of Nile tilapia (Oreochromis niloticus) microRNAs response to Streptococcus agalactiae infection through high-throughput sequencing. (July 2016) - Wang, Bei; Gan, Zhen; Cai, Shuanghu; Wang, Zhongliang; Yu, Dapeng; Lin, Ziwei; Lu, Yishan; Wu, Zaohe; Jian, Jichang
Abstract: MicroRNAs are a kind of small non-coding RNAs that participate in various biological processes. Deregulated microRNA expression is associated with several types of diseases. Tilapia ( Oreochromis niloticus ) is an important commercial fish species in China. To identify miRNAs and investigate immune-related miRNAs of O. niloticus, we applied high-throughput sequencing technology to identify and analyze miRNAs from tilapia infected with Streptococcus agalactiae at a timescale of 72 h divided into six different time points. The results showed that a total of 3009 tilapia miRNAs were identified, including in 1121 miRNAs which have homologues in the currently available databases and 1878 novel miRNAs. The expression levels of 218 tilapia miRNAs were significantly altered at 6 h–72 h post-bacterial infection (pi), and these miRNAs were therefore classified as differentially expressed tilapia miRNAs. For the 1121 differentially expressed tilapia miRNAs target 41961 genes. GO and KEGG enrichment analysis revealed that some target genes of tilapia miRNAs were grouped mainly into the categories of apoptotic process, signal pathway, and immune response. This is the first report of comprehensive identification of O. niloticus miRNAs being differentially regulated in spleen in normal conditions relating to S. agalactiae infection. This work provides an opportunity for further understanding of the molecular mechanisms of miRNA regulation in O. niloticus host-pathogen interactions. Highlights: miRNA profile of tilapia was performed by Solexa deep sequencing. A total of 1121 conserved and 1878 novel miRNAs were identified. Many miRNAs were differentially regulated during Streptococcus agalactiae infection in vitro. Target prediction indicated that a number of miRNAs involved in immunity.